The effect of Fe2+ state in electrical property variations of Sn‐doped hematite powders. Issue 9 (5th May 2017) - Song, Sehwan; Kim, Jiwoong; Lee, Dooyong; Lee, Jisung; Min, Taewon; Chae, Jong‐Ah; Bae, Jong‐Seong; Lee, Jaekwang; Lee, Jeong‐Soo; Park, Sungkyun
Abstract: The structural, electrical, and chemical properties of Sn‐doped Fe2 O3 powders were investigated. Various quantities of Sn‐doped Fe2 O3 powders were synthesized using solid‐state reactions. Rietveld analysis for the powders that were doped below 2% revealed a phase‐pure Sn‐doped Fe2 O3 structure (i.e., identical to Fe2 O3 structure). Alternatively, the analysis for the powders that were doped more than 3% exhibited secondary phase. The unit cell volume and electrical conductivity of the phase‐pure samples increased with an increase in the doping concentration. X‐ray photoelectron spectroscopy measurements showed an increased Fe 2+ state with the increase in Sn doping concentration. Therefore, the improved electrical conductivity and unit cell volume with the increase in doping concentration of the phase‐pure powders might be related to the increased Fe 2+ state.